VIEWS OF MALE COMMUNITY ELDERS WITH REGARDS TO TRADITIONAL MALE CIRCUMCISION AT A CLINIC IN LIMPOPO PROVINCE, SOUTH AFRICA - Mathule, Azwianewi; Mothiba, Tebogo (Southern African Journal of Social Work and Social Development, 2016)
This study explored the views of male community elders on traditional male circumcision at a clinic in the Limpopo Province. A qualitative research was conducted. The researchers used exploratory and descriptive design to guide the process of this study. Purposive sampling was followed and 18 male community elders between the ages of 40 to 75 years were interviewed. Semi-structured individual interviews were conducted and data were analysed using the Tesch’s open-coding data analysis method. One theme with six subthemes emerged. The study found that traditional male circumcision had several unexpected and unsafe outcomes. It predisposes males to infections and bad environmental conditions. The period when the circumcision is performed could be viewed as a moral teaching session and the lessons learned could prepare boys for manhood. The study recommended that the National Department of Health should conduct workshops and training sessions for traditional circumcisers. This should include a focus on maintaining sterility during circumcision, in order to safeguard the initiates from becoming infected.